Exemplary Teacher Selection Using a VIKOR-Based Decision Support System - Dwipa Handayani; Dani Yusuf; Gabriella Putri Larasati; Ozzi Ardhiyanto (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2024)
Yadika 13 Tambun Vocational School has criteria where the school does not yet have a system that can support a decision. The decision support system (DSS) for selecting exemplary teachers in appreciating teacher performance presentations that have been made while teaching staff is expected to increase motivation so that they can improve their performance. Many DSS methods are used to find a decision in this study. The method to be used is VIseKriterijumska Optimizacija I Kompromisno Resenje, (VIKOR) which can produce the best alternative in the form of ranking of an existing sample by looking at the utility values and weights of each sample. This study describes the design of a decision support system for conducting assessments in selecting exemplary teachers at SMK Yadika 13 Tambun. System design using UML (Unified Modeling Language). The decision support system (DSS) is very helpful for those who will carry out the assessment process, before there was a decision support system the school always found it difficult to assess because it took quite a long time, the assessment was still done manually, it was difficult to calculate the assessment, sometimes there is an error in the assessment results. Therefore, this decision support system, it can help the school minimize these problems.